PERBANDINGAN KEHILANGAN BOBOT PADA PEMBUATAN RACIKAN TEOFILIN-TRIAMCINOLONE MENGGUNAKAN ALAT PERACIKAN BLENDER DAN MORTIR - Inez Angelia; Ari Tanti (Jurnal Kesehatan, 2022)
A prescription is a written request from a doctor or dentist to a pharmacist, either in paper or electronic form, to provide and deliver drugs to patients in accordance with applicable regulations. Concoction drugs are drugs that are formed by changing or mixing drug preparations or active ingredients. The number of requests for compounding affects the waiting time for compounded drugs in pharmaceutical installations, so compounding using a blender really helps the concocters to be faster in dispensing and speed up waiting times. This study aims to find out how much weight is lost in the mixture of one of the pulmonary doctors at the Santo Borromeus Hospital if it is mixed using a different compounding tool and to find out which tool is better to use in the compounding of 30 capsules of theophylline 70 mg and triamcinolone 2 mg. The research was conducted by weighing the initial weight of the compound to be formulated, and weighing the final weight after it was mixed. Then calculated the weight loss and hypothesis testing were carried out using the Mann-Whitney U Test. The results of the weight loss test using a blender, a lot of powder is lost, the average powder loss is 4.28%, while the results from the weight loss test using a mortar are less powder lost, the average powder loss is 0.54%. The results showed that in this case compounding made using a mortar was better than compounding using a blender.